2015
DOI: 10.1021/jp5129657
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Noncovalent Interactions in the [n]Cycloparaphenylene⊃C70 (n = 10, 11, and 12) Host–Guest Complexes: A Theoretical Insight into the Shortest C70–Carbon Nanotube Peapod

Abstract: The encapsulations of fullerene C 70 by carbon-nanorings are of great interest because, unlike the spheroidal C 60 , several distinct geometrical orientations are possible. Additionally, due to experimental difficulties, there is a great deal of opportunity for the computational efforts to deeply explore the intrinsic nature of π−π noncovalent interactions of the CPP carbon-nanoring⊃fullerene host−guest systems. In this paper, the structures and properties of the host−guest complexes formed with nanoring host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 68 publications
6
58
0
Order By: Relevance
“…As a result, they capably identify the spatial extent and the underlying nature of interactions present in molecular systems and complexes. The relevance of NCI for studying large systems has been demonstrated on DNA, proteins, as well as nanotubes, 205,206 polymers, 207 and crystals under high pressure. 208 Moreover, this tool has also been used to explore reactivity, 114,184,209,210 dynamics, 191 and solvation 211 effects.…”
Section: Applicability and Usefulness Of Visualization Toolsmentioning
confidence: 99%
“…As a result, they capably identify the spatial extent and the underlying nature of interactions present in molecular systems and complexes. The relevance of NCI for studying large systems has been demonstrated on DNA, proteins, as well as nanotubes, 205,206 polymers, 207 and crystals under high pressure. 208 Moreover, this tool has also been used to explore reactivity, 114,184,209,210 dynamics, 191 and solvation 211 effects.…”
Section: Applicability and Usefulness Of Visualization Toolsmentioning
confidence: 99%
“…Given the low polarity of most fullerenes, noncovalent interactions involving fullerenes are often dominated by dispersion, so most fullerene receptors are designed trying to maximize the fullerene‐receptor contact surface . In this way, different fullerene receptors have been proposed such as cycloparaphenylenes, porphyrins, and others . For this purpose, an interesting opportunity is to exploit the so‐called concave–convex π‐π interaction using buckybowls as receptors .…”
Section: Introductionmentioning
confidence: 99%
“…9 The surface modified non-covalent complexes of CNTs are stabilized by van der Waals, electrostatic, p-p stacking, C-HÁ Á Áp and charge transfer interactions. [10][11][12][13][14][15] The developments made in the field of functionalized CNTs have been summarized in a review by Meng et al 16 Both experimental and theoretical studies have revealed that the complexes of single-walled carbon nanotubes (SWCNTs) possess enhanced electronic properties compared to free carbon nanotubes and can be used in electronic devices. 5,[17][18][19] The functionalization of CNTs alters their optical properties to a large extent as noticed in the CNT-squarylium complex in which the squarylium dye has been reported as a photosensitizer.…”
Section: Introductionmentioning
confidence: 99%